Theoretical Foundations of Education: contributions of the Psychology of Mathematics Education of the Early Years of Elementary School L (Research, Society and Development, 2020)
The central scope of this research addresses the Psychology of Mathematics Education for professionals with a degree in Pedagogy courses, focusing on teachers who exercise the  teaching of mathematics teaching in the early years of elementary school I. This article analyzes and presents the potentialities and contributions of this theoretical field of knowledge in       the teaching-learning  process of Mathematics. Education aiming at improvements of the Brazilian student in the external evaluations of the Brazil Test published by the SAEB of 2017 and 2019, as well as the pedagogical practice between teacher-student-knowledge. It was justified the insufficient proficiency in mathematics of Brazilian students of about 70%, as well as the reduced number of scientific productions on the theme of this article. The objective of this study was to present contributions of the Psychology of Mathematics Education in the early years of elementary school I. On the methodological path, it was characterized within the qualitative approach and in the procedures of bibliographic research. Among the main results were the discourses of the interviewed subjects pointing out the potentiality of the theoretical basis of Psychology of Mathematics Education in their pedagogical knowledge/doing. It was found that the psychological, cognitive and affective-social dimension have implications for students' learning. It concludes an emergence of a further discussion of this field of knowledge in the degree of pedagogy courses in Brazil to increase the quality of pedagogical intervention of pedagogue teachers in mathematics classes, aiming to increase the quality teaching-learning process of mathematics in the early years and the results of institutional and large-scale evaluations.